The results of using Blue cap® foam for skin care with signs of xerosis - T.V. Svyatenko; O.A. Starostina; S.V. Zakharov; S.V. Solovyiova (Medičnì Perspektivi)
A significant increase in the severity of clinical manifestations of various dermatoses accompanied by dry skin often increases the feeling of discomfort and itching of the skin, significantly reducing the patient's quality of life. This leads to the search for effective ways to correct the dryness of the skin and maintain the proper functioning of the epidermal barrier of the skin in various dermatoses. The aim of the study was to study the effect of using a combined emollient, which includes components of a classic emollient (with the inclusion of ceramides and substances with moisturizing and softening effects), as well as substances with antiseptic and fungistatic effects. The results of treatment of 100 patients with skin diseases and conditions accompanied by dry skin and itching were analyzed. The study group included patients with acne undergoing treatment with retinoids and external preparations with an irritating effect, patients with atopic dermatitis in remission, patients with seborrheic dermatitis, rosacea, follicular hyperkeratosis, and skin xerosis. Using the method of corneometry, the dynamics of changes in skin hydration during the use of a combined moisturizer and changes in the indicators of the dermatological index of the quality of life of patients were studied. The data obtained showed a pronounced increase in skin hydration in terms of corneometry after 2 weeks of using an emollient (by an average of 31.6 units or 160%), and after a month of observation, the changes amounted to 36.7 conv. units, i.e. increased by 185%, which proves the effectiveness of using Blue cap® foam to normalize skin hydration. The level of the dermatological index of quality of life during this period decreased from 9.9±0.2 to 7.2±0.2 points, i.e. by 2.7 points or 27%,what also indicates an improvement in the subjective attitude of patients and promotion quality of life of patients. In the course of the study, a significant improvement in skin hydration when using the combined Blue cap® foam to correct signs of skin xerosis was proven. In the case of dermatoses accompanied by itching associated with dry skin, a marked reduction in itching was noticed, as well as a significant improvement in the quality of life of the patient after a month of using the combined moisturizer.